2018
DOI: 10.1111/jvim.15289
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tamoxifen for the treatment of severe equine asthma

Abstract: BackgroundTamoxifen, a selective estrogen receptor modulator, decreased airway neutrophilia and improved clinical signs in an experimental model of equine asthma, and induced neutrophilic apoptosis in vitro.Hypothesis/ObjectivesTamoxifen reduces airway neutrophilia and improves lung function in severe asthmatic horses.AnimalsTwelve severe asthmatic horses from a research herd.MethodsRandomized controlled blinded study design. The effects of a 12‐day oral treatment with tamoxifen (0.22 mg/kg, q24h) or dexametha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…These differences might make the clinical effect of TX on respiratory burst questionable and warrants further testing in order to determine the actual clinical applicability of these results. A recent, independent study evaluated the clinical effect of orally dosed TX in horses with severe equine asthma and could not demonstrate clinical improvement; although airway resistance was reduced, there was no significant improvement in BALF neutrophil counts (Mainguy‐Seers, Picotte, & Lavoie, ). Thus, no conclusions should be made regarding clinical applicability of TX until further data are available.…”
Section: Discussionmentioning
confidence: 99%
“…These differences might make the clinical effect of TX on respiratory burst questionable and warrants further testing in order to determine the actual clinical applicability of these results. A recent, independent study evaluated the clinical effect of orally dosed TX in horses with severe equine asthma and could not demonstrate clinical improvement; although airway resistance was reduced, there was no significant improvement in BALF neutrophil counts (Mainguy‐Seers, Picotte, & Lavoie, ). Thus, no conclusions should be made regarding clinical applicability of TX until further data are available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our data also showed that TX has the ability to induce in vivo apoptosis of granulocytic cells in a model of induced acute lung inflammation in horses, with concomitant clinical improvement (Perez et al., 2016). An independent group also found that TX produces an improvement in airway resistance in horses with exacerbated severe equine asthma, although no significant improvement in BALF neutrophil counts was observed in that study (Mainguy‐Seers, Picotte, & Lavoie, 2018). Thus, no conclusions should be made regarding the clinical applicability of TX until further data are available.…”
Section: Introductionmentioning
confidence: 90%
“…In this study, we determined pharmacokinetic parameters of TAM in adult horses. The few clinical studies that have looked into the potential use of TAM for equine airway inflammation have been based on a single dosage (approximately 0,25 mg/kg) extrapolated from human medicine, with conflicting results regarding clinical efficacy based on that single empirical dose [15,16]. However, there is robust pre-clinical information on modulation of inflammation, which warrants the pharmacokinetic and safety data presented here [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, a single administration of 0.25 mg/kg of TAM was used. This dose was originally extrapolated from standard human dosages [48], and was the same dose used in previous equine clinical studies [15,16]. The drug was administered after 8 h of overnight fasting.…”
Section: Tam Administrationmentioning
confidence: 99%